Inferno ebook A novel. - Brown, Dan (Robert Langdon, 2013)
THE #1 WORLDWIDE BESTSELLER FROM THE ICONIC AUTHOR OF THE DA VINCI CODE AND THE LOST SYMBOL “A book-length scavenger hunt . . . jam-packed with tricks.” — The New York Times “[A] cinematic blockbuster.” — USA Today Harvard professor of symbology Robert Langdon awakens in an Italian hospital, disoriented and with no recollection of the past thirty-six hours, including the origin of the macabre object hidden in his belongings. With a relentless female assassin trailing them through Florence, he and his resourceful doctor, Sienna Brooks, are forced to flee. Embarking on a harrowing journey, they must unravel a series of codes, which are the work of a brilliant scientist whose obsession with the end of the world is matched only by his passion for one of the most influential masterpieces ever written: Dante Alighieri’s The Inferno . Robert Langdon returns in Origin and The Secret of Secrets (coming soon)!